2022
DOI: 10.3390/jcm11061719
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Patients Presenting with Post-Intubation Upper Airway Complications: A Parallel Epidemic?

Abstract: During the current pandemic, we witnessed a rise of post-intubation tracheal stenosis (PITS) in patients intubated due to COVID-19. We prospectively analyzed data from patients referred to our institution during the last 18 months for severe symptomatic post-intubation upper airway complications. Interdisciplinary bronchoscopic and/or surgical management was offered. Twenty-three patients with PITS and/or tracheoesophageal fistulae were included. They had undergone 31.85 (±22.7) days of ICU hospitalization and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 41 publications
6
26
0
Order By: Relevance
“…This number almost doubled after the COVID19 pandemic, with 24 referrals during the 15-month study period. In concurrence with previous studies, we observed a disproportionate number of obese patients, with an even higher incidence of patients with DM (41.7% versus 17.4%) [ 7 ]. Obesity is a well described risk factor for PITS/PTTS in pre-pandemic studies and also complicates the course of acute COVID19 with a higher rate of MV and airway management issues among these patients [ 3 , 8 ].…”
supporting
confidence: 92%
See 3 more Smart Citations
“…This number almost doubled after the COVID19 pandemic, with 24 referrals during the 15-month study period. In concurrence with previous studies, we observed a disproportionate number of obese patients, with an even higher incidence of patients with DM (41.7% versus 17.4%) [ 7 ]. Obesity is a well described risk factor for PITS/PTTS in pre-pandemic studies and also complicates the course of acute COVID19 with a higher rate of MV and airway management issues among these patients [ 3 , 8 ].…”
supporting
confidence: 92%
“…The wide time window between extubation, clinical presentation and diagnosis was also almost identical to previous reports [ 7 ]. Interestingly, more patients in our study presented with simple stenosis than in previous reports where complex stenosis was more common [ 7 , 12 ]. Complex stenosis was significantly more common among PTTS patients.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…They suggest that steroid intake prolongs the presence of COVID-19 virus in the GI tract, resulting in increased possibility of severe GI manifestation including PI [8]. Interestingly, there are increasing numbers of patients who developed airway strictures after intubation for COVID-19 infection [9], this may prompt further looking into the inflammatory response due to COVID-19 infection, as there might be specific pathways at the molecular level that induce excessive fibrotic and structuring response to COVID-19 infection, whether in the respiratory tract or GI as in our case.…”
Section: Discussionmentioning
confidence: 99%